Online and on-campus transfer students experienced different impacts from the pandemic - Ardissone, Alexandria N.; Galindo, Sebastian; Triplett, Eric W.; Drew, Jennifer C. (Frontiers in Education, 2023)
The COVID-19 pandemic caused extensive disruption to higher education, highlighting the negative impacts of emergency shift to online instruction. As a result, advantages of intentionally designed, online programs in higher education were overshadowed during the pandemic. Furthermore, socioeconomic disparities were exacerbated during the pandemic which extended to STEM undergraduate transfer students, who are more likely to be low-income, from historically underrepresented groups, older, and first generation in their family to attend college. To better understand the impact of the pandemic on STEM undergraduates, including those in an intentionally designed online program, ordinal regression analysis of 352 student survey respondents enrolled in a life sciences major at a large, R1 institution in the United States spring 2020 through fall 2021 was performed. Three student types are compared: on-campus, first-time in college (FTIC); on-campus transfer (OC-TR); and online transfer (ONL-TR) students. The latter group receives all course delivery online, whereas on-campus student groups received predominately in-person course delivery prior to the pandemic. ONL-TR students were over 6 times less likely to report negative educational impact compared to on-campus students, FTIC and OC-TR, while controlling for parent education, income, gender, race/ethnicity, and GPA. Additional survey items further explored this result and were validated with academic records and thematic analysis of students’ text responses. A pre-/post-pandemic comparison revealed that students maintained a similar course load and GPA, despite increased perceptions of a lower GPA during the pandemic. OC-TR students were over 2 times more likely to express increased concern related to delayed graduation and higher frequency of feeling stress compared to FTIC and ONL-TR students. Meanwhile, low-income students were more likely to report stressors due to the pandemic’s impact on daily life, independent of student type. Taken together, students in this intentionally designed online program were more resilient to the educational and emotional impacts of the pandemic compared to on-campus students. The differences between student groups warn against generalization of student impacts and suggest further research into the positive role of online learning, not just for delivery of educational content and expanding access, but for academic and emotional stability for different student populations.